THE EFFECT OF PARITY AND LIFESTYLE ON THE INCIDENCE OF LOW BIRTH WEIGHT IN MOTHERS WITH SEVERE PRE-ECLAMPSIA - Riski Sahara; Dhiyan Nany Wigati (The Shine Cahaya Dunia Kebidanan, 2023)
Background; BBLR is the highest cause of neonatal death in 2022. One of the complications of pre-eclampsia in mothers is the birth of a baby with low body weight and premature birth, supported by the theory explaining that parity is one of the factors that influence the incidence of low birthweight. Today people's lifestyles are shifting with the consumption of many unhealthy foods and other habits that affect the decline in health status, especially in pregnant women. Method; The research design is quantitative research using case and control design (case control) and retrospective approach. Using 64 samples divided into 32 samples for the case group and 32 samples in the control group. Result; The results of this study analysis showed a significant relationship between parity and lifestyle with the incidence of low birth weight in mothers with severe pre-eclampisa characterized by a p value of 0.002 and 0.000, respectively. parity has a greater influence on the incidence of BBLP in pre-eclampsia mothers than on lifestyle. Conclusion; Parity and lifestyle have a significant relationship with the incidence of low birth weight in mothers with severe pre-eclampsia. Parity has a greater influence on the incidence of severe birth in mothers with Pre-eclampsia.